Infrared study of the carbochlorination of MoO3 with gaseous chlorine below 703 K - Guibaldo, Cristina Noemi (2016)
In this work the kinetics of the carbochlorination of molybdenum trioxide with sucrose carbon at low temperatures (below 703 K) has been studied by IR. A novel methodology for studying reaction kinetics is proposed based on on-line IR measurements of gaseous reaction products. This technique allows identification of all the species involved in the reaction system which were not taking into account in previous studies. As predicted by thermodynamic calculations, the reaction proceeds by formation of CO2 mainly, however formation of CO, COCl2, CCl4 and HCl also takes place. The starting temperature for the reaction is determined at about 600 K. A reaction mechanism is proposed based on the analysis of binary interactions between the reactants and their morphological changes during the reactions. The influence of carbon/oxide ratio, gaseous flow rate, sample initial mass, temperature, and chlorine partial pressure in the reaction rate was analyzed. Two kinetic regimes were identified, with activation energies of 203 ± 13 and 36 ± 6 kJ mol−1 which were attributed to chemical reaction control (below 653 K) and mixed reaction control at high temperatures. A reaction order of 0.5 with respect to chlorine partial pressure at 673 K was determined for the carbochlorination reaction.